A study on safety and efficacy of intralesional vitamin D3 in cutaneous warts - Potlapati, Amruthavalli; Gangaiah, Narendra; George, Neethu Mary (International Journal of Research in Dermatology, 2020)
Background: Immunotherapy is an upcoming treatment modality for cutaneous warts. Majority of the treatment modalities used for warts are destructive and can be painful, causes scarring and are not suitable for multiple warts. Immunotherapy overcome these shortcomings and it has shown good response both in injected and distant warts. Literature shows only very limited data on the use of immunotherapy, especially vitamin D3, in case of cutaneous warts. Objective was to evaluate the safety and efficacy of intralesional vitamin D3 in cutaneous warts and to assess the treatment response and adverse effects of the same. Methods: Sixty patients of age more than 18 years of both sexes with cutaneous warts were given intralesional vitamin D3 of maximum five doses two weeks apart after obtaining an informed written consent. Patients were monitored for reduction in size and number of warts and also for any side effects. Results: Out of the total 60 patients, 46 (76.6%) patients had complete resolution of warts following injection, 12 (20%) cases showed partial response and 2 (3.4%) cases had no response. Conclusions: Intralesional vitamin D3 was found to be an effective treatment modality for multiple and recalcitrant warts.